Defining Hair Follicles in the Age of Stem Cell Bioengineering - Chuong, Cheng-Ming (J Invest Dermatol, 2007)
One challenge faced by stem cell biologists is the bioengineering of an organ. Ehama et al. (2007, this issue) used cells derived from human and rodent epidermis and dermal papilla to reconstitute hair-follicle mini-organs. Some result in hair follicles; others are hair follicle–like. The challenge calls for the development of a set of criteria to define a hair follicle so that bioengineered products in the future can be evaluated.